Economic impacts of implementing a national smoke-free prison policy. (30th September 2020) - McMeekin, N; Hunt, K; Brown, A; Tweed, E; Pell, J; Craig, P; Leyland, A; Conaglen, P; Boyd, K
Abstract: Background: Worldwide, over 600, 000 non-smokers are killed annually due to exposure to secondhand smoke (SHS); the UK societal cost of SHS is estimated at £700million per annum. Prior to recent smoke free policy in Scottish prisons smoking rates were very high (70-75%), well above population rates, subjecting people in custody (PiC) and prison staff to high levels of SHS. Eradicating SHS exposure in prisons could lead to improved health in previous smokers and non-smokers alike, and decrease demand on the National Health Service. However, to date, there is little evidence relating to the economic impact of smoking bans in prisons. Methods: An economic evaluation estimating the short-term and lifetime impacts of smokefree prison policy in Scotland policy used data from the TIPs study (Jun 2016-Nov 2019) for prison staff and PiC. The analyses adopted a public health and personal perspective and key resources included: implementation costs, cessation support services, health service use and personal costs. For the short-term analyses data were sourced from TIPs staff and PiC surveys, and routine data from the Scottish Prison Service and NHS National Services Scotland. Outcomes included SHS exposure, staff sickness absence, violent incidents and quality adjusted life years (QALYs). The life-time analysis used a Markov model to estimate cost per QALY for both staff and PiC. Results: SHS exposure measures show a median reduction of 91%. Costs and economic outcome results (mean cost pre- and post-ban, cost-consequences balance sheet and incremental cost per QALYs) are confidential until May 2020 due to their sensitivity and will be available to present at EUPHA 2020. Conclusions: Previous economic evaluations have focussed on smoking bans in public places and raising the smoking age. This is the first economic analysis of a national prison smoking ban and analysis will be of interest to prison services in other jurisdictions which have yet to implement smokefree policy.